Multi-parametric analysis of ciprofloxacin toxicity at ecologically relevant levels: short- and long-term effects on Daphnia magna - Dionísio, Ricardo (2022)
The increased presence of emergent compounds, such as pharmaceuticals drugs, in the aquatic compartment has been acknowledged as an evolving environmental issue whose consequences are not yet fully characterized. Specific classes of pharmaceutical drugs, such as fluoroquinolone antibiotics, can exert toxic effects to non-target species with ecological significance, since these compounds are environmentally stable and persistent, and may interact with some of the key physiologic processes of organisms. Despite such characteristics, knowledge about the effects of these drugs is still scarce, especially to non-target organisms. The present study aimed to evaluate the effects of chronic and acute exposures of the cladoceran Daphnia magna to the fluoroquinolone antibiotic ciprofloxacin. Putative toxic effects were assessed, following acute and chronic exposures to ecologically relevant concentrations of ciprofloxacin, through enzymatic (cholinesterase - ChEs, catalase - CAT, glutathione S-transferases - GSTs) and non-enzymatic (thiobarbituric acid reactive substances - TBARS, glycogen - Gly) biomarkers. In addition, we also determined behavioural (swimming distance - SD) and morphological (body length of the first brood - BL1B) endpoints in animals exposed to this drug. Ciprofloxacin acute exposure resulted in increased CAT and ChEs activities, and inhibited GSTs activity. After chronic exposure, ChEs activity was significantly inhibited, while GSTs activity was significantly enhanced. TBARS levels were only increased at higher concentrations of ciprofloxacin. CAT activity and Gly content did not evidence a clear and significant pattern of variation. SD was slightly inhibited during dark cycles. BL1B presented a significant decrease for animals subjected to an intermediate concentration. Results showed that even ecologically relevant concentrations of ciprofloxacin may cause oxidative stress in individuals of D. magna. The present study showed important data that corroborate the occurrence of significant biochemical alterations in key features of an aquatic organism when exposed to relevant levels of a widely used antibiotic, establishing essential links between environmental exposure to this specific drug and putative toxic challenges that may result in irreversible changes and damages, especially at the individual level. However, changes in the size of neonates suggest that population alterations are likely to occur under real scenarios of chronic contamination by this drug.